Synergetic integration of vertical farms and buildings: reducing the use of energy, water, and nutrients - Blom, Tess; Jenkins, Andy; van den Dobbelsteen, Andy (Frontiers in Sustainable Food Systems, 2023)
Vertical farms use some resources very efficiently. However, their electricity use is considerable, and a significant amount of waste heat is produced. This paper investigates how the integration of vertical farms in buildings could reduce the use of energy, water, and nutrients collectively across both entities by leveraging potential resource synergies. The paper considered the integration of vertical farms in apartments, offices, restaurants, swimming pools, and supermarkets located in the Netherlands. For each typology, the floor area heated and the amount of building users fed by one m2 of one production layer within the vertical farm was calculated, along with required outputs of water and nutrients from the building to sustain the vertical farm. The energy savings of different integration strategies were calculated for each building typology in comparison to a non-integrated approach. Results showed that the synergetic integration of vertical farms with buildings reduced the year-round energy use of the climate systems of both entities collectively by between 12 and 51%. The integration of vertical farms with buildings decreases the use of energy, water, and nutrients from external sources and offers great potentials to reduce the environmental impacts of both entities, whilst producing food in urban environments.